Drought tolerant forb flora of a semi-arid protected savanna in the Lowveld of South Africa - van Coller, H.; Klem, J.; Siebert, F. (African Biodiversity & Conservation, 2021)
Background: Increased frequency and intensity of droughts related to climate change are predicted to induce pressure on herbaceous communities. Considering that forbs contribute significantly to savanna ecosystem resilience, we investigated forb communities of a protected semi-arid savanna during an extensive drought. Objective: We identified drought-tolerant species with their related functional traits. Results: Drought-tolerant forb flora comprised of several plant families and species with overlapping traits, of which the ability to resprout was related to perennials, whereas succulence and prostrate growth form were typical annual forb dominance traits. Conclusion: Results highlight the functional importance of forbs and their resilience to drought events in protected areas.